Recent Developments in the Assessment of Nutrition Knowledge in Athletes - Tam R; Gifford JA; Beck KL (Springer Science+Business Media, LLC, 2022)
Purpose of Review Adequate nutrition knowledge may influence dietary behaviour, and the performance and health of athletes. Assessment of the nutrition knowledge of athletes can inform practice and provide a quantitative way to evaluate education interventions. This article aims to review nutrition knowledge questionnaires published in the last 5 years to identify advances, possible improvements in questionnaire development and design, and challenges that remain. Recent Findings Twelve new or modified questionnaires were identified. All had undergone validity and reliability testing. Advancements included quantitative measures of content validity and Rasch analysis. Online questionnaires were common, with at least seven using this format. Advances included use of images (n=2), automated scored feedback (n=1), and use of applied questions. Summary While advancements have been made in validation and reliability testing and electronic delivery, new questionnaires would benefit from interactive and attractive features including images, provision of electronic feedback, and applied questions.
Keywords: Athlete knowledge; Knowledge questionnaire; Nutrition knowledge; Questionnaire development; Reliability; Sports nutrition; Validity; Athletes; Health Knowledge, Attitudes, Practice; Humans; Nutritional Status; Reproducibility of Results; Surveys and Questionnaires